The future of plant virology in Africa - Thresh, Michael (Technical Centre for Agricultural and Rural Cooperation, 1998)
Dr Michael Thresh is Honorary Professor of Plant Virus Ecology at the Natural Resources Institute, University of Greenwich, UK. He first worked in Ghana (1953-1960) and then returned to the UK. From 1970 onward, he undertook numerous assignments in...